Patient-specific 3D-printed nasopharyngeal stents in dogs: a cadaveric pilot study - Sutter, Craig; Hardy, Brian; Lucero, Steven; Johnson, Lynelle; Culp, William (Frontiers in Veterinary Science, 2024)
BackgroundCurrently available treatment options for nasopharyngeal stenosis and imperforate nasopharynx in dogs and cats are fraught with complications and failures.ObjectiveTo develop patient-specific nasopharyngeal stents using 3D-printed molds and to assess placement and fit of stents within the nasopharynx.AnimalsSix canine cadavers.MethodsPatient-specific nasopharyngeal silicone stents were generated using 3D-printed molds based on CT scans. A placement protocol was developed. Post-placement, goodness of fit within the nasopharynx was evaluated and compared to currently used methods. Mechanical properties of silicone stents were compared to catheter-based and nitinol stents.ResultsDevelopment and placement of stents was successful in all six cadavers. Silicone stents offered stiffness (force required for compression, N) and post-load deformation comparable to nitinol stents (1.8–6.2 vs. 1.2–3.3 N and 0.02–0.08 vs. 0.01–0.14 mm, respectively). Patient-specific stents offered superior goodness of fit in the nasopharynx (81–90%) compared to bilateral red rubber catheters (16.2–33.8%).ConclusionDevelopment and placement of patient-specific stents using 3D printed molds was successful in all six cadavers. The novel stents exhibited similar mechanical properties and superior goodness of fit compared to commercially available stents, potentially offering a better alternative to commercially available stents. Further investigation is needed in animals with nasopharyngeal stenosis to determine efficacy and to assess utility in live patients.